Expanding the genotypes and phenotypes for 19 rare diseases by exome sequencing performed in pediatric intensive care unit. Issue 11 (15th August 2021) - Liu, Juan; Zheng, Yu; Huang, Jiaotian; Zhu, Desheng; Zang, Ping; Luo, Zhenqing; Yang, Yongjia; Peng, Yu; Xiao, Zhenghui; Zhu, Yimin; Lu, Xiulan
Abstract: Phenotypes of some rare genetic diseases are atypical and it is a challenge for pediatric intensive care units (PICUs) to diagnose and manage such patients in an emergency. In this study, we investigated 58 PICU patients (39 deceased and 19 surviving) in critical ill status or died shortly without a clear etiology. Whole exome sequencing was performed of 103 DNA samples from their families. Disease‐causing single‐nucleotide variants (SNVs) and copy number variants (CNVs) were identified to do genotype‐phenotypes analysis. In total, 27 (46.6%) patients received a genetic diagnosis. We identified 34 pathogenic or likely pathogenic SNVs from 26 genes, which are related to at least 19 rare diseases. Each rare disease involved an isolated patient except two patients caused by the same gene ACAT1 . The genotypic spectrum was expanded by 23 novel SNVs from gene MARS1, PRRT2, TBCK, TOR1A, ECE1, ARX, ZEB2, ACAT1, CPS1, VWF, NBAS, COG4, and INVS . We also identified two novel pathogenic CNVs. Phenotypes associated with respiratory, multiple congenital anomalies, neuromuscular, or metabolic disorders were the most common. Twenty patients (74.1%) accompanied severe infection, 19 patients (70.1%) died. In summary, our findings expanded the genotypes and phenotypes of 19 rare diseases from PICU with complex characteristics. Abstract :